A conditional depreciation balancing strategy for the equitable operation of extended hybrid energy storage systems. (15th October 2018) - Fan, Feilong; Huang, Wentao; Tai, Nengling; Zheng, Xiaodong; Hu, Yan; Ma, Zhoujun
Graphical abstract: Highlights: Proposes a conditional depreciation balancing strategy. Proposes a novel integrated virtual battery model. Proposes a multiscale searching algorithm to equalize the conditional depreciations. The energy storage units with different energy features are utilized fully. The life depreciation rate of extended hybrid energy storage systems is decreased. Abstract: Various history life depreciations and energy characteristics of the facilities in the hybrid energy supply system challenge the conventional balancing strategies, which mostly aim to address the state-of-charge imbalance issues. This paper proposes a conditional depreciation balancing strategy to cope with the stated challenge. The conditional depreciation balancing strategy is based on extended hybrid energy storage systems, which consist of supercapacitors, batteries and equivalent battery storage units corresponding to heating systems. An integrated virtual battery model is adopted in the equivalent process of the heating system. The conditional depreciation is innovatively defined to evaluate the operation equitability of the extended hybrid energy storage systems. The equalization of the conditional depreciation is achieved by a multiscale searching algorithm. The proposed conditional depreciation balancing strategy is validated by a hybrid energy supply system of a four-floor building in Shanghai, China. Test results show that the fast dynamic response ability of the supercapacitors and the high energy density of the integrated virtual battery models are utilized fully by the proposed conditional depreciation balancing strategy. The maximum power changing rate of the supercapacitors, integrated virtual battery models and batteries is 0.86 kW/s, 0.03 kW/s, and 0.22 kW/s, respectively. The 24-h charging/discharging energy of the supercapacitors, integrated virtual battery models and batteries is 7.80 kWh, 18.37 kWh and 5.21 kWh, respectively. Compared to the state-of-charge balancing strategy, the proposed conditional depreciation balancing strategy decreases the maximum imbalance coefficient of the energy storage units by 82.74%. The life depreciation rate and the life depreciation cost of the extended hybrid energy storage system decrease by 47.05% and 53.85%, respectively.